2014
DOI: 10.1177/0022034514521237
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Biglycan Promotes Bone Morphogenetic Protein-induced Osteogenesis

Abstract: The aim of this study was to determine the effects of glutathione-S-transferase-fused recombinant biglycan (GST-BGN) on craniofacial bone regeneration. We recently demonstrated a positive effect of tissue-derived BGN on bone morphogenetic protein 2 (BMP-2) function, which is exerted likely via the BGN core protein. Here, we investigated the effects of GST-BGN lacking any posttranslational modifications on BMP-2 function in vitro and in vivo. In the C2C12 cell culture system, BMP-2-induced Smad 1/5/8 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…In contrast, genes that were minimally expressed in cardiac fibroblasts were induced in a specific temporal manner during the course of osteogenic differentiation (Figure 1C) and included sets of genes known to regulate inflammation, extracellular matrix proteins and cell metabolism (Figure S1A). Next, we created an osteogenic signature based on a set of 37 genes that are induced during osteogenic differentiation (Chen et al, 2012);(Choi et al, 2010);(Graneli et al, 2014);(Harkness et al, 2011);(Hoshiba et al, 2009);(Liu et al, 2013);(Miguez et al, 2014);(Nora et al, 2012);(Olivares-Navarrete et al, 2011) (Figure S1B). We used the mean fold change in expression of this set of genes to quantitatively determine an osteogenic signature and observed that compared to control cardiac fibroblasts, cardiac fibroblasts subjected to osteogenic differentiation progressively adopted an osteogenic signature (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, genes that were minimally expressed in cardiac fibroblasts were induced in a specific temporal manner during the course of osteogenic differentiation (Figure 1C) and included sets of genes known to regulate inflammation, extracellular matrix proteins and cell metabolism (Figure S1A). Next, we created an osteogenic signature based on a set of 37 genes that are induced during osteogenic differentiation (Chen et al, 2012);(Choi et al, 2010);(Graneli et al, 2014);(Harkness et al, 2011);(Hoshiba et al, 2009);(Liu et al, 2013);(Miguez et al, 2014);(Nora et al, 2012);(Olivares-Navarrete et al, 2011) (Figure S1B). We used the mean fold change in expression of this set of genes to quantitatively determine an osteogenic signature and observed that compared to control cardiac fibroblasts, cardiac fibroblasts subjected to osteogenic differentiation progressively adopted an osteogenic signature (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Many roles have been assigned to members of this protein family including modulation of extracellular matrix organization, matrix adhesion, cellular proliferation and growth factor sequestration; the latter function modulating BMP and TGFb signaling. Biglycan and fibromodulin have been shown to modulate key cartilage, tendon, and bone cell signaling factors such as BMP2, BMP4, TLR4 ligands, TGFb1, TGFb2, TGFb3, and Wnt through binding of these ligands [32][33][34][35][36]. This interaction is mediated through the SLRP GAG chains [37] or the core protein [36] and has been proposed to allow sequestration of the ligands within the extracellular matrix [38].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is mediated through the SLRP GAG chains [37] or the core protein [36] and has been proposed to allow sequestration of the ligands within the extracellular matrix [38]. Through its ability to modulate BMP signaling and thus osteoclasts, biglycan is a key regulator of bone mineralization [32]. In addition, biglycan has been shown to induce the expression of osteogenic factors via TLR2 activation in aortic valve interstitial cells inducing valve calcification leading to aortic valve stenosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Given the magnitude of biglycan interactome, it is not surprising that this SLRP leads to organ-specific effects encompassing renal diseases (Kuroda et al, 2004, Moreth et al, 2010, Moreth et al, 2014, Schaefer et al, 2004, Stokes et al, 2000), bone formation and healing (Berendsen et al, 2014, Chen et al, 2004, Desnoyers et al, 2001, Miguez et al, 2014), muscular dystrophy (Bowe et al, 2000, Rafii et al, 2006), control of neuromuscular synapses (Amenta et al, 2012) and autoimmune perimyocarditis (Popovic et al, 2011). In addition, biglycan has been recently linked to cancer cell proliferation (Hu et al, 2014, Niedworok et al, 2013).…”
Section: Introductionmentioning
confidence: 99%